Global Financial Crisis and Its Ramifications on Capital Markets Opportunities and Threats in Volatile Economic Conditions - Hacioğlu, Ümit; Dinçer, Hasan (Contributions to Economics, 2017)
XIX, 659 p. 113 illus., 104 illus. in color.